MENELISIK KONTROVERSI RIBA DAN BUNGA BANK (Analisis Penelusuran Hadis) - Fadel, Muhammad; Ilyas, Abustani; Tasbih, M (At-Tuhfah : Jurnal Studi Keislaman, 2022)
This study aims to examine the controversy of usury and bank interest through the search for various hadith about usury. This research is a library search with a descriptive qualitative approach. The data in this study are secondary data obtained from various journals and research related to the discussion. The results showed that in addition to the Qur'an the prohibition of usury has also been widely narrated in various sahih hadith. Related to usury and bank interest, there are still pros and cons between scholars because of differences in the basis and understanding of interpreting the proposition. But in essence, the prohibition of usury is very clear even though the addition is only a little bit.